Association of miRNA − 320 expression level and its target gene endothelin-1 with the susceptibility and clinical features of polycystic ovary syndrome - Nearmeen M. Rashad; Marwa Abdel-Monem Ateya; Yasser S. Saraya; Walid Mohamed Elnagar; Khaled Fathy Helal; Mohamed El-Bakry Lashin; Amr Ahmed Abdelrhman; Ayman E. Alil; Mohammed S. Yousef (BMC, 2019)
Abstract Background Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disorder characterized by obesity, hyperandrogenism, and insulin resistance (IR). MicroRNAs (miRNAs) are small noncoding RNA associated with ovarian follicle development and female fertility. The objective of this study was to investigate the role of miRNA- 320 and its target gene endothelin-1 (ET-1) as a noninvasive biomarker of PCOS and to evaluate its possible relationship with IR as well as clinic-morphological features of PCOS. Methods Case-control study enrolled 60 patients with PCOS and 40 control group. We subdivided our PCOS women according to homeostasis model assessments of insulin resistance (HOMA-IR) to PCOS women with and without IR.ET-1 levels were measured by ELISA. We estimated the serum expression level of miRNA- 320 by real-time polymerase chain reaction. Results Our results revealed that serum miR-320 expression level was lower in PCOS patients compared to controls, in particular, PCOS women with IR. Moreover, it was negatively correlated to its target gene; ET-I as well as fasting serum insulin (FSI), HOMA-IR, PCOS phenotype; hirsutism score, ovarian volume and antral follicle count (AFC). In the PCOS group, linear regression analysis revealed that only hirsutism and HOMA-IR was the main predictor of expression levels of miRNA − 320 among other clinical and laboratory biomarkers of PCOS. The sensitivity and specificity of serum miR-320 expression levels in diagnosis PCOS was 80, and 97.5% respectively. Conclusion The Expression serum levels of miR-320 were lower in PCOS compared to control and it could be a noninvasive diagnostic biomarker of PCOS.